Experimental demonstration of the thermodynamic advantage of modular heat storage system for a variable-temperature input. (October 2019) - Singh, Manmeet; Bhattacharya, Jishnu
Highlights: Experiments are done for multi-tank modular sensible heat storage system. The input flow is of variable temperature to mimic intermittent solar heat input. Charge-discharge protocols are decided by relative input-storage temperatures. The enthalpic and exergetic efficiencies are compared with conventional storage. Remarkable gain in performance metrics is observed as quantified by cost analysis. Abstract: Storage acts as an inseparable component of the heat accumulation process using an inherently intermittent and variable source such as solar heat. Sensible thermal storage often is chosen over the other options owing to its operational simplicity and lower response time. In the current study we propose a novel method of designing the sensible heat storage system which can provide significantly better energetic and exergetic efficiency particularly under variable temperature profile for the input flow as compared to the conventional single tank storage. Through small scale laboratory experiments, we demonstrate the proof of concept for the proposed modular multi-tank storage against a low temperature input flow having prescribed temperature variations. We observe that for both charging and discharging, the modular storage holds a distinct thermodynamic advantage due the thermal segregation as well as the appropriate sequencing of the use of different tanks based on heat transfer argument. The concept of modular thermal storage can remarkably enhance the flexibility of plant operation and improve the energetic and exergetic efficiencies of the storage.